The Effectiveness of Constructive Learning Having a Vision of Science, Environment, Technology, Society for Increase Results Learn IPA High School Student - Gunaria Siagian*; Lufri Lufri; Andromeda Andromeda; Fatni Mufit (JIPI (Jurnal IPA dan Pembelajaran IPA), 2023)
Developing students' abilities in science is one of the successful means of increasing their ability to adapt to changing times and enter the world of science, environment, technology, and social life. This study aims to analyze the application of the SETS vision of a constructivist approach to science learning in Class X SMA Negeri 3 Pematang Siantar . SETS (science, environment, technology and society) insightful learning that connects and links the theory learned with its application in the form of technology, its impact on society and the environment as well as social is a form of business that has real and contextual characteristics . This research is a quantitative study with a quasi-experimental method with nonequivalent control group design. The research sample was determined by purposive sampling technique which was divided into 2 classes, namely the experimental class and the control class. The data analysis technique used is the independent sample t-test. The results of the study found that the use of animated video-based learning media was very effective in applying to the physics learning process in terms of the posttest questions and the gain test scores also increased by 0.71 in the experimental class and 0.57 in the control class which was included in the medium category. So it can be concluded that the constructivism learning model is effective in improving physics learning outcomes.